Dari Eksperimen Milgram ke Budaya Digital: Tinjauan Literatur tentang Evolusi Konformitas dan Kepatuhan di Era Modern - Ningsih, Desri; Neviyarni, Neviyarni (TSAQOFAH, 2026)
Conformity and obedience are two central concepts in social psychology, yet their transformation within digital culture has received relatively limited systematic attention. This study aims to examine the evolution of conformity and obedience from classical perspectives to the digital era and to identify new forms of social influence mediated by algorithms, online norms, and platform interaction mechanisms. Adopting a qualitative approach with a systematic literature review design, the study analyzes 52 scholarly publications selected through purposive sampling from various academic databases. Data were collected through structured searches and analyzed using thematic analysis to identify patterns, conceptual shifts, and new configurations of social influence. The findings reveal fundamental changes in the mechanisms of social influence in digital spaces, where digital signals such as likes, followers, algorithmic recommendations, and visibility indicators of popularity function as new forms of normative pressure and symbolic authority. These results contribute to the refinement of social influence theory by introducing the dimensions of digital conformity and digital obedience, and by expanding understanding of how human behavior is shaped by the architecture and structures of digital media. The study underscores the importance of digital literacy and critical awareness of algorithmic mechanisms to reduce vulnerability to online social influence and opens avenues for further research on variations in digital influence across different user groups and social media platforms.